Praktik Restorative Justice Pada Lembaga Pemasyarakatan (LP) Di Perancis, New Zealand dan Arab Saudi: Sebuah Perbandingan - Fitria Fitria (SALAM: Jurnal Sosial dan Budaya Syar-i, 2015)
The description of the article below will discuss the practice of restorative justice in correctional institutions in three countries: France, New Zealand and Saudi Arabia. The selection of these three countries is based on two reasons, first: the three countries represent three different legal systems: the continental legal system, the anglo saxon system and the Islamic legal system. Second, the three countries mentioned above have the capacity to represent the ideas developed by their respective legal systems. France is an old country that has contributed a lot in building the idea of restorative justice. New Zealand is an Anglo Saxon country that has successfully implemented restorative justice in its correctional institutions. Meanwhile, Saudi Arabia is a country that is considered an Islamic country that is the most consistent in implementing Islamic criminal law which also has a concept of restorative justice.Keywords: Restorative Justice; Correctional Institution; France; New Zealand; Saudi Arabia Abstrak:Paparan tulisan dibawah ini akan membahas praktik restorative justice pada Lembaga Pemasyarakatan di tiga negara: Perancis, New Zealand dan Arab Saudi. Pemilihan tiga negara ini berdasarkan pada dua alasan, pertama: ketiga negara mewakili tiga sistem hukum yang berbeda: sistem hukum kontinental, sistem anglo saxon dan sistem hukum islam. Kedua, ketiga negara yang disebutkan diatas memilki kapasitas untuk mewakili gagasan yang dikembangkan masing-masing sistem hukum. Perancis merupakan negara tua yang memberikan kontribusi yang tidak sedikit dalam membangun gagasan restorative justice. Adapun New Zealand merupakan negara anglo saxon yang sukses menerapkan restorative justice pada Lembaga Pemasyarakatannya. Sedangkan Arab Saudi merupakan negara yang dianggap sebagai negara islam yang paling konsisten menerapkan hukum pidana islam yang juga memiliki konsepsi restorative justice.Kata Kunci: Restorative Justice; Lembaga Pemasyarakatan; Perancis; New Zealand; Arab Saudi